Spectral Domain Optical Coherence Tomography Findings of Subacute Sclerosing Panencephalitis Presenting with Macular Necrotizing Retinitis: A Case Report - ÇAM, FURKAN; DERİCİOĞLU, VOLKAN; ÇELİKER ATABERK, HANDE (My University, 2022)
Purpose: To report the fundus photographs and spectral domain optical coherence tomography (SD-OCT) findings of a patient with subacute sclerosing panencephalitis (SSPE) presenting merely with ocular symptoms. Case report: A 20-year-old patient presented with sudden loss of vision in the left eye (LE). Fundus photograph showed a yellow lesion in the macula and SD-OCT showed increased reflectivity of the inner retinal layers. Disorganization of the necrotizing retinal layers in the LE gradually progressed to the atrophic retina. Then, visual complaints began in the right eye (RE) accompanied by neurological symptoms. SD-OCT revealed the inner and outer plexiform layers edema and interruption of the ellipsoid zone in RE. Fundus photographs showed macular atrophy for both eyes on the day patient died. Conclusion: This case report demonstrates the SD-OCT findings of SSPE retinitis with close follow-up from the acute retinitis to the total atrophic macula. These unique findings may be considered as characteristical for the diagnosis.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; OFTALMOLOJİ; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Optometri; Oftalmoloji; Optometry; Ophthalmology; Macular necrotizing retinitis; measles virus; moth-eaten appearance of retina; optical coherence tomography; subacute sclerosing panencephalitis; Macular necrotizing retinitis; measles virus; moth-eaten appearance of retina; optical coherence tomography; subacute sclerosing panencephalitis